2005
DOI: 10.1590/s0102-05362005000300005
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos quantitativos e qualitativos de melão cultivado sob doses de fertilizantes orgânicos

Abstract: O melão (Cucumis melo L.), adapta-se bem a regiões caracterizadas por climas quentes e com alta intensidade luminosa. Os estados do Rio Grande do Norte e Ceará apresentam excelentes condições edafoclimáticas para o seu cultivo, o que possibilitou no ano de 2003, exportar aproximadamente 150 mil toneladas de frutos, gerando receita, ao redor dos 58 milhões de dólares (SECEX/DTIC, 2004). Diante da importância desta cultura para a região, há uma grande demanda de informações visando definir um sistema produtivo S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Melon is cultivated throughout the year in Brazil's semiarid, allowing the producers to supply specific windows in the international market (Freitas et al, 2007), occupying a prominent place in Brazil's vegetables growing and becoming an export product (Pinto et al, 2008). Sales Júnior et al (2005) reports that melon adapts well to regions characterized by warm climates and high luminous intensity. Furthermore, is favored by low precipitation indices, once it decrease disease incidence and increases fruit's quality (Mesquita et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melon is cultivated throughout the year in Brazil's semiarid, allowing the producers to supply specific windows in the international market (Freitas et al, 2007), occupying a prominent place in Brazil's vegetables growing and becoming an export product (Pinto et al, 2008). Sales Júnior et al (2005) reports that melon adapts well to regions characterized by warm climates and high luminous intensity. Furthermore, is favored by low precipitation indices, once it decrease disease incidence and increases fruit's quality (Mesquita et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of this culture to the region, there is a enormous demand for information trying to define a productive system that presents cost-saving, increases productivity, and achieve the minimum standards of fruit quality that are demanded in the international market, this being one of Brazilian horticulture biggest challenges (Sales Júnior et al, 2005). Ribeiro et al (2014) after to evaluate the effect of organic and mineral source in melon production and development in Piauí state south region, concluded that manure can be used as unique source to fertilize melon plant, as alternative way to chemical fertilizer, which can give the producer profitability.…”
Section: Introductionmentioning
confidence: 99%